Contribucion al conocimiento y control de las enfermedades del pino piñonero - Fonseca-Nieves, N.=700 1 De Azevedo, N.
(Es, En)
ilus., 8 ref.
Keywords: PINUS; ENFERMEDADES DE LAS PLANTAS; MYCORRHIZAE; SINTOMAS; CONTROL QUIMICO; ESPAÑA; PINO PIÑONERO; CENANGIUM ABIETIS